Pengembangan Tracking Kesehatan Berkala Berbasis Web pada Sivitas Akademika Universitas Nasional Karangturi - Penta Putri Nunik Yuniarti; Dody Indra Sumantiawan (KOLONI, 2026)
Universitas Nasional Karangturi currently does not have a web-based periodic health tracking system to support the management and monitoring of health information for its academic community. Consequently, the university has not yet established an integrated platform for recording health data, maintaining health histories, or providing reliable health information to support decision-making related to campus health services. This study aims to develop a web-based periodic health tracking system for the academic community of Universitas Nasional Karangturi. The research employed the Research and Development (R&D) method using the Waterfall software development model, which consists of requirements analysis, system design, implementation, testing, and maintenance. Data were collected through observation, interviews, and literature review. The system was developed using Laravel 12 as the framework, PHP 8.2 as the programming language, MySQL as the database management system, XAMPP as the local web server environment, and Figma for designing the user interface. The developed application provides features including user authentication, user management, health record management, health history, health information, health references, periodic health examination scheduling, and a support ticketservice. The implementation of User Interface (UI) and User Experience (UX) principles ensures that the system is intuitive, efficient, and user-friendly for both administrators and users. Functional testing was conducted using the Black Box Testing method, and the results demonstrated that all system features performed according to the specified functional requirements without critical errors. Therefore, the proposed system is considered suitable for implementation as a digital solution to support periodic health tracking and improve health information management for the academic community at Universitas Nasional Karangturi.